Dental implant survival rate in well-controlled diabetic patients. A systematic review. - Heber Arbildo; César Lamas; Dora Camara; Hernán Vásquez (Universidad de Concepción., 2015)
Background: Dental implants have now become one of the most popular options for replacing a missing tooth. On the other hand, diabetes mellitus is a systemic disease that affects a large part of the population and is generally considered an absolute or relative contraindication to implant therapy. Aim: To determine the survival rate of dental implants in controlled diabetic patients through a systematic review. Material and methods: A systematic search in Pubmed, SciELO and RedALyC databases was performed. The selection criteria were: studies published in the last 10 years, with at least 20 controlled diabetic patients, reporting survival rate and number of implants placed, with follow-up periods equal to or longer than 1 year, including a control group of healthy patients. Methodological quality was analyzed with the follwing scales: Jadad and Downs & Black's CMQ. Results: Three articles with a follow-up period between 1 and 12 years were analyzed. The overall survival rate of dental implants in diabetic controlled patients was 97.43%. Conclusion: The reviewed literature suggests that survival rate of dental implants in well-controlled diabetic patients is similar to non-diabetic patients.